2018
DOI: 10.1371/journal.pone.0207081
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist long protocol versus GnRH antagonist protocol for various aged patients with diminished ovarian reserve: A retrospective study

Abstract: This retrospective analysis compared the efficiency of the gonadotropin- releasing hormone (GnRH) antagonist (GnRH-ant) protocol and the GnRH agonist long (GnRH-a) protocol for patients with diminished ovarian reserve (DOR). A total of 1,233 patients with DOR (anti-Mullerian hormone <1.1 ng/mL) were recruited for this retrospective case-control study. They were divided into two groups according to female age. Younger patients were assigned to POSEIDON group3 (PG3: age ≤35 years); older patients were assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
2
29
1
Order By: Relevance
“…Long-acting GnRH agonist may result in excessive ovarian suppression. Therefore, the conventional ovarian stimulation protocols are mainly mild ovarian stimulation and GnRH antagonist protocols for DOR patients [7,8,10,13]. However, in our present study, our data indicate that long-acting GnRH agonist could improve endometrial thickness and clinical outcomes of IVF for young DOR patients.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Long-acting GnRH agonist may result in excessive ovarian suppression. Therefore, the conventional ovarian stimulation protocols are mainly mild ovarian stimulation and GnRH antagonist protocols for DOR patients [7,8,10,13]. However, in our present study, our data indicate that long-acting GnRH agonist could improve endometrial thickness and clinical outcomes of IVF for young DOR patients.…”
Section: Discussioncontrasting
confidence: 53%
“…To attempt to optimize in vitro fertilization (IVF) outcomes for DOR, a lot of treatments have been proposed, such as different ovarian stimulation protocols, luteal phase pretreatments and various supplements and modi cations during ovarian stimulation [7][8][9][10][11]. However, most of the therapeutic strategies had limited success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• GnRH analogues (3,25,26) • Androgens (25) • GH cotreatment (25,27) • Natural cycle or modified natural cycle (25) • High dose gonadotropins (25) • Glucocorticoids 3• Coenzyme Q10 (28) • Acupuncture (29) • Holistic medicine (25) • Autologous Platelet-Rich Plasma • In-vitro activation of follicles • Combination of the above (25).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…Huang et al have recently compared the efficiency of the GnRHa vs GnRH antagonist protocols in 1233 POR patients (26). They have found a lower cancellation rate (10 vs. 22%), higher implantation rate (25.3 vs. 10.7%), and higher LBR (27.6 vs. 13%) in young POR patients (POSEIDON group 3), but not in the older POR patients (POSEIDON group 4), undergoing the GnRH agonist COS protocol than in those using the antagonist protocol (26). They concluded that the agonist protocol was more effective than the antagonist protocol for young POR patients (26).…”
Section: Gnrh Analoguesmentioning
confidence: 99%